Control of cell adhesion and migration by podocalyxin. Implication of Rac1 and Cdc42 - Fernández, Darío (2013)
Podocalyxin (PODXL) is a type I membrane sialomucin, originally described in the epithelial cells (podocytes) of kidney glomeruli. PODXL is also found in extra-renal tissues and in certain aggressive tumors, but its precise pathophysiological role is unknown. Expression of PODXL in CHO cells enhances their adhesive, migratory and cell?cell interactive properties in a selection and integrin-dependent manner. We aimed at defining the PODXL domains responsible for those cell responses. For this purpose we have analyzed the cell adhesion/migration responses to deletion mutants of human PODXL, and the correlation with the activities of Rac1 and Cdc42 GTPases. The results obtained indicate that integrity of the PODXL ectodomain is essential for enhancing cell adhesion but not migration, while the integrity of the cytoplasmic domain is required for both adhesion and migration. Deletion of the carboxy-terminal DTHL domain (PODXL-ΔDTHL) limited only cell adhesion. The activities of Rac1 and Cdc42 GTPases parallel the PODXL-induced variations in cell adhesion and migration. Moreover, silencing the rac1 gene virtually abolished the effect of PODXL in enhancing cell adhesion.